Maximizing the Benefits of Internationalization: The Moderating Role of Labour Flexibility - Jung, Heung-Jun; Noh, Sung-Chul; Chung, Sun-Wook (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2016)
SummaryUsing the large-scale Korean Workplace Panel Survey, this study examines the interplay between international diversification, labour flexibility, and workplace-level performance in the context of advanced emerging markets. Filling the gap in the literature on the international diversification-performance (IDP) relationship, which focuses primarily on firm-level characteristics and overlooks the role of labour factors as contingent variables, we draw attention to the workplace level dynamics by exploring how the two types of labour flexibility—functional and numerical flexibility—moderate the impact of international diversification on performance. The results show that when workplaces invest in training for job enlargement and employee involvement programs that lead to the enhancement of functional flexibility, the link between international diversification and performance can be strengthened.This finding supports the assertion in the international HRM literature that, in the ever-globalized business environment, investment in human capital is a better strategy for improving financial performance in the long run. Furthermore, we find that numerical flexibility, as measured by in-house subcontracting arrangements, has a negative impact on the IDP relationship. Overall, our study suggests that the quality of human resources and a well-designed workplace configuration may still help improve performance in the context of international diversification, whereas excessive dependence on employment externalization for cost reduction is likely to hurt not only financial performance but also long-term sustainability. We also believe that our findings on the advanced emerging market economy complement insights from previous studies, which are largely based on Western developed economies, thus enriching current theories on labour flexibility.